Application study of UAV path planning based on the balanced search factor artificial bee colony algorithm - Hao, Wenlong; Luo, Bo; Zhang, Zhiyuan (Journal of physics. Conference series, 2021)
In this paper, aiming at the shortcomings of slow convergence speed and weak local search ability of traditional artificial bee colony algorithm in path planning, an artificial bee colony algorithm based on balanced search factor is proposed for UAV path planning. Using a search strategy based on balanced search factor, the depth search is carried out while maintaining a certain population diversity. The global search ability and local development ability are balanced, the average accuracy of path planning is improved, the robustness of path planning is enhanced, and the ability to obtain better path solutions is improved.